Roti dan Roti Tak-Beragi: Elemen Perjamuan Masa Lalu yang Masih Berlaku hingga Kini - Rasid Rachman (Theologia in Loco, 2020)
There is a narrative in the word. The narrative tells the way of life. The way of life draws the theology of society in daily life. One of the people daily life is a meal. A meal is not only the need of life but also the social rite. One element of the meal is bread. The Bible tells about two kinds of bread, namely: the bread and the unleavened bread. Those two kinds of bread motivated me to find out how the Bible distinguishes both the meaning and practice of those bread. The use of the bread and the unleavened bread narrate the society daily life and ritual both ancient Israel and the Christianity of the first century around the Mediterranean. The Bible gives that narrative to us. I search both word and practice of the bread and the unleavened bread with the meal of the Jews, as being told by the Old Testament and the New Testament especially the early Christianity. The point of this article is the deserve element of the Eucharist of the Church today: the bread or the unleavened bread. Above all, even though the tradition of the Church told one of those elements, we should open our mind to contextualization.